Inventory Analysis of Spare Part Using Always, Better, Control (ABC) and Economic Order Quantity (EOQ) Method in PT. XYZ - Medan - Nofan Hadi Ahmad; Wahyu Fitrianda Mufti; Tri Novita Sari; Asri Amalia Muti; Yulfadila Yulfadila (Jurnal IPTEK, 2025)
Inventory plays a pivotal role in a company's logistics, serving both to fulfill external customer demands and to enhance internal production efficiency. However, PT. XYZ in Medan did not address yet several cost factors that could significantly influence the overall procurement expenses of spare parts, particularly given that certain spare parts carry notably high purchase prices. While PT. XYZ has been placing orders for spare parts, these are typically initiated only when stock is depleted, based on the assumption that spare parts fall under the category of slow-moving goods. Consequently, it is imperative to conduct an inventory analysis to identify gap between the existing conditions and the outcomes derived from the proposed methodological approach. The methodology used in this study is Always, Better, Control (ABC) method to classify spare parts based on their cost percentage and Economic Order Quantity (EOQ) method to analyze the economic order size, order frequency and optimal ordering time. From the results of data processing that has been done, there are 7 types of spare parts that fall into category A and there is a decrease in Total Variable Cost (TVC) ranging from 13% to 40% from existing conditions. Ordering costs consist of telecommunications costs, labor costs, fuel costs and loading/unloading costs; while storage costs consist of electricity costs and maintenance costs. Scheduling the time of reordering or sending purchase order (PO) to the vendor, the number of spare part units to be ordered and the estimated arrival of spare parts are carried out based on the EOQ calculation that has been compared and adjusted to the previous existing conditions.